Sediment-mediated coupling of hyporheic exchange and land use drives macroinvertebrate community structure - Mengdan Guan; Wei Hong; Nan Li; Jinxi Song; Guobin Fu; Shilei Yang; Haoying Zhang; Mengyang Yang; Haozheng Sun (Journal of Cleaner Production, 2026)

High-resolution chronostratigraphic framework and spatiotemporal evolution of Carboniferous-Permian source rocks in the Junggar Basin and its periphery - Zhangshuai Hou; Xiangdong Wang; Dongming Zhi; Yong Tang; Qiong Wu; Hua Zhang; Jian Cao; Dongsheng Xiao; Guobin Fu; Menglin Zheng; Xuefeng Qi; Yaofeng Cai; et al. (Science China Earth Sciences, 2026)

An innovative theoretical model for optimizing ball diameter in tumbling mills - Yunxiao Li; Qingfei Xiao; Yanxiong Fu; Saizhen Jin; Guobin Wang; Mengtao Wang; Boyuan Sun; Houyuan Tian; Xiaobo Liu; Jiahao Tian (Minerals Engineering, 2025)

Quantifying Impacts of Human Activities and Climate Change on Runoff Variation: A Case Study of Songhua River Basin, China - Wenhan Pei; Jiping Liu; Yanhui Chen; Guobin Fu; Chongya Ma; Yufei Liu (Chinese Geographical Science, 2025)

A new approach to color correction and equalization for generating mars global color image mosaics from Tianwen-1 MoRIC images - Xin Ren; Xiaoxia Zhang; Wangli Chen; Wei Yan; Xingguo Zeng; Xu Tan; Xingye Gao; Qiang Fu; Lin Guo; Qing Zhang; Zhaopeng Chen; Guobin Yu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Deep soil carbon pool responses to climate change in the Chinese Loess Plateau - Guangyao Gao; Binbin Li; Karl J. Niklas; Yuanyuan Huang; Mingxiang Xu; Guobin Liu; Bojie Fu (Science Bulletin, 2025)

Attributions of Rainfall Anomalies to Weather Systems and Their Spatial and Temporal Variabilities: A Case Study of Victoria in Southeast Australia - Guobin Fu; Francis H. S. Chiew; David A. Post; Acacia Pepler; Irina Rudeva (International Journal of Climatology, 2024)
Attributions of rainfall anomalies to weather systems and their spatio‐temporal variability in Victoria, southeast Australia are investigated with a multimethod weather type dataset and two popularly used gridded daily rainfall datasets for the period 1979–2015. The rainfall anomalies before, during and after the Millennium Drought (1997–2009) are compared to quantify the temporal variability of rainfall responses to weather type changes. The results show: (1) Three weather systems (Front, Cyclone and Thunderstorm) and their combinations contribute 89% of total rainfall; (2) Contributions of weather types to rainfall vary from month to month with winter season rainfall coming from more diverse weather types than summer rainfall; (3) The contributions of weather types to rainfall in three periods show temporal variabilities and there is a clear shift of contribution pattern after the Millennium Drought, such as front‐thunderstorm (FT) is now the largest contributor to rainfall compared with cyclone‐frontal‐thunderstorm (CFT) before and during the Millennium Drought; (4) A seasonal shift in the post‐drought period is found with higher rainfall in February and March and lower rainfall in September and October. The increased rainfall in February mainly results from Front–Thunderstorm (FT) and Thunderstorm‐only (TO), while rainfall declines in September from all weather types; (5) Several rainfall characteristics that are important for streamflow generation, such as rainfall intensity, probability of rainfall occurrence, number of rainfall days and the maximum daily rainfall, do depend on the weather types; (6) The results are similar with different rainfall datasets, but differences do exist, especially at the local scale. The conclusions of this study are drawn from an Australian case study but have implications for other regions to investigate the attributions of rainfall characteristic changes to weather systems.

Trend and inter-annual variability in regional climate models – Validation and hydrological implications in southeast Australia - Jin Teng; James C. Bennett; Steve Charles; Francis Chiew; Fei Ji; Nick Potter; Guobin Fu; Marcus Thatcher; Tomas Remenyi (Journal of Hydrology, 2024)

Unraveling deformation mechanism of the Fukang fold-and-thrust belt: Insight into intracontinental orogenesis of the Bogda Mountain, NW China - Yu Zhen; Dengfa He; Xuan Chen; Di Li; Guobin Fu; Wenjian Guo (Marine and Petroleum Geology, 2024)

Geochemical characteristics of the upper carboniferous source rocks in a terrestrial-marine transitional environment from the shuangjingzi area, Junggar Basin: Insights into palaeoenvironment, palaeoclimate, and palaeovegetation - Xue Chen; Xiao Jin; Xinjian Zhu; Wenren Zeng; Guobin Fu; Zhihuan Zhang (Marine and Petroleum Geology, 2024)

Biomass carbon stock and allocation of planted and natural forests in the Loess Plateau of China - Binbin Li; Guangyao Gao; Karl J. Niklas; Yiqi Luo; Mingxiang Xu; Guobin Liu; Bojie Fu (Agricultural and Forest Meteorology, 2024)

A 76-m per pixel global color image dataset and map of Mars by Tianwen-1 - Jianjun Liu; Xin Ren; Wei Yan; Wangli Chen; Xingguo Zeng; Xiaoxia Zhang; Xu Tan; Xingye Gao; Qiang Fu; Dingxin Liu; Lin Guo; Qing Zhang; et al. (Science Bulletin, 2024)

Distribution and dynamics of niche and interspecific association of dominant phytoplankton species in the Feiyun River basin, Zhejiang, China - Shengnan Zhu; Zengchuan Dong; Guobin Fu; Shujun Wu; Jinyu Meng; Weilin Liu; Yupeng Liu; Xun Cui; Yuejiao Zhou (Journal of Oceanology and Limnology, 2024)

Geochemical characteristics and formation mechanism of organic-rich source rocks of mixed sedimentary strata in continental saline lacustrine basin: A case study of Permian Pingdiquan formation in the Shishugou Sag, Junggar Basin, Northwest China - Wenren Zeng; Boran Wang; Xuan Chen; Guobin Fu; Zhihuan Zhang; Zhilong Huang (International Journal of Coal Geology, 2024)

Episodic evolution of intracontinental orogenic deformation: Insight from the southern Bogda fold-and-thrust belt of the Tianshan Mountains, NW China - Yu Zhen; Dengfa He; Di Li; Xuan Chen; Guobin Fu (Tectonophysics, 2024)

A new approach of coupled long-range forecasts for streamflow and groundwater level - David E. Robertson; Guobin Fu; Olga Barron; Geoff Hodgson; Andrew Schepen (Journal of Hydrology, 2024)

Exploring the potential for groundwater-related ground deformation in Southern New South Wales, Australia - Pascal Castellazzi; Wolfgang Schmid; Guobin Fu (Science of The Total Environment, 2023)

Formation mechanism of organic-rich mixed sedimentary rocks in saline lacustrine basin, Permian Lucaogou Formation, Jimsar Sag, Junggar Basin, Northwest China - Wenren Zeng; Zhihuan Zhang; Boran Wang; Xuan Chen; Ruihui Zheng; Guobin Fu; Ying Jin (Marine and Petroleum Geology, 2023)

A top-down deep learning model for predicting spatiotemporal dynamics of groundwater recharge - Xin Huang; Lei Gao; Nan Zhang; Russell S. Crosbie; Long Ye; Jian Liu; Zhaoxia Guo; Qinghua Meng; Guobin Fu; Brett A. Bryan (Environmental Modelling & Software, 2023)

Adaptation to climate change through strategic integration of long fallow into cropping system in a dryland Mediterranean-type environment - Chao Chen; Noboru Ota; Bin Wang; Guobin Fu; Andrew Fletcher (Science of The Total Environment, 2023)

Downscaling algorithms for annual TRMM data based on climatic and orographic variables over the Qinling Mountains, China - Qing Meng; Ranjan Sarukkalige; Guobin Fu; Guan Wang; Wenhao Jia; Zhuang Liu; Hongying Bai; Xiaobang Peng; Shanhong Zhang (Theoretical and Applied Climatology, 2023)

Carbon stock and sequestration of planted and natural forests along climate gradient in water-limited area: A synthesis in the China's Loess plateau - Binbin Li; Guangyao Gao; Yiqi Luo; Mingxiang Xu; Guobin Liu; Bojie Fu (Agricultural and Forest Meteorology, 2023)

Trends and variability of rainfall characteristics influencing annual streamflow: A case study of southeast Australia - Guobin Fu; Francis H.S. Chiew; David A. Post (International Journal of Climatology, 2023)
The trend and variability in rainfall characteristics that influence annual streamflow of southeast Australia is assessed using two methods, non‐parametric Kendall test and linear slope, and two gridded daily rainfall datasets (SILO and AWAP) and 1,196 station rainfall data for 1971–2021 period. The rainfall anomaly before, during and after the Millennium Drought (1997–2009) is compared to quantify the variability. The results show: (a) a declining rainfall trend is detected as the recent dry decades were preceded by wet decades. The declining trend largely occurs from autumn through to spring with the largest trend in August to October followed by April and May; (b) the trend is more significant for number of rainfall days and for multi‐day rainfall totals (and more so for longer accumulations) than for annual rainfall; (c) the very high extreme rainfall shows a small increasing trend in summer and mixed signal in the other seasons; (d) the streamflow in the post drought period is lower than the long‐term mean, despite the mean annual rainfall being slightly higher. This can be partly explained by the rainfall‐runoff relationship of catchments not having fully recovered from the prolonged drought and partly by changes in rainfall characteristics, like the wet spell length and multi‐day rainfall, influencing annual streamflow; (e) The general conclusions for analyses with different sources of daily rainfall data are the same. However, some differences do exist, with SILO gridded rainfall and station data having larger areas with statistically significant trend than the AWAP gridded rainfall, as well as larger declining trends in the high elevation areas. The general conclusions of this study are drawn from an Australia case study but could have implications for other regions to investigate the attributions of rainfall characteristics other than annual rainfall to the non‐stationary rainfall‐streamflow relationship.

Uncertainty of Gridded Precipitation at Local and Continent Scales: A Direct Comparison of Rainfall from SILO and AWAP in Australia - Guobin Fu; Olga Barron; Stephen P. Charles; Michael J. Donn; Thomas G. Van Niel; Geoff Hodgson (Asia-Pacific Journal of Atmospheric Sciences, 2022)

Annual and seasonal precipitation trends and their attributions in the Qinling Mountains, a climate transitional zone in China - Qing Meng; Hongying Bai; Ranjan Sarukkalige; Guobin Fu; Wenhao Jia; Chenhua Zhang (Theoretical and Applied Climatology, 2021)

Climate changes and variability in the Great Artesian Basin (Australia), future projections, and implications for groundwater management - Guobin Fu; Yuanchun Zou; Russell S. Crosbie; Olga Barron (Hydrogeology Journal, 2020)

Evaluation of HHT approach for estimating agricultural drought trend and frequency based on modified soil water deficit index (MSWDI) - Huicai Yang; Huixiao Wang; Guobin Fu; Haiming Yan; Panpan Zhao (Theoretical and Applied Climatology, 2019)

From meteorological droughts to hydrological droughts: a case study of the Weihe River Basin, China - Panpan Zhao; Haishen Lü; Wenchuan Wang; Guobin Fu (Arabian Journal of Geosciences, 2019)

Generation of multi-site stochastic daily rainfall with four weather generators: a case study of Gloucester catchment in Australia - Guobin Fu; Francis H. S. Chiew; Xiaogang Shi (Theoretical and Applied Climatology, 2018)

Screen for Inhibitors of Crystal Growth to Identify Desirable Carriers for Amorphous Solid Dispersions Containing Felodipine - Jinping Fu; Lin Cui; Congbin Yang; Hui Xiong; Guobin Ren; Xingyuan Ma; Qiufang Jing; Fuzheng Ren (AAPS PharmSciTech, 2018)

The Physicochemical Investigation of 17β-Estradiol Crystalline Prepared by In Situ pH-Dependent Solubility Technique with Polyvinylpyrrolidone - Hui Xiong; Jinping Fu; Hanjing Sun; Enfu Wang; Yunhui Ding; Guobin Ren; Qiufang Jing; Fuzheng Ren (AAPS PharmSciTech, 2017)

Comparison of NCEP ‐ NCAR and ERA ‐Interim over Australia - Guobin Fu; Stephen P. Charles; Bertrand Timbal; Branislava Jovanovic; Fen Ouyang (International Journal of Climatology, 2016)
This study compares observations of 22 climate variables [rainfall, minimum and maximum temperature, mean sea level pressure (MSLP), and air temperature, geopotential heights, relative and specific humidity, and u‐wind and v‐winds at 500 , 700 and 850 hPa] over Australia with NCEP‐NCAR (National Centers for Environmental Prediction‐National Center for Atmospheric Research) and ERA ‐Interim, two most often used reanalysis products. The results indicate that both NCEP‐NCAR and ERA ‐Interim generally reproduce the observed spatial patterns of long‐term mean annual rainfall, daily maximum/minimum temperature and MSLP, the monthly distribution (annual cycle) of rainfall and temperature, although temperature is generally better simulated than rainfall and ERA ‐Interim shows an overall better performance than NCEP‐NCAR in term of continental scale. In term of linear trends, both NCEP‐NCAR and ERA ‐Interim simulate observed trend signs in some regions, but not in others, and the spatial distributions of temperature trends are generally not as well simulated as that of annual rainfall for both NCEP‐NCAR and ERA ‐Interim. In addition, NCEP‐NCAR and ERA ‐Interim show similar spatial patterns of annual mean air temperature, geopotential heights, humidity and winds. This implies that studies using NCEP‐NCAR data could also make use of ERA ‐Interim to explore the range of uncertainties for the regions and climate variables where NCEP‐NCAR and ERA ‐Interim show differences. This conclusion may also apply to regions other than Australia. For example, the different trend signs of MSLP between NCEP‐NCAR and ERA ‐Interim could present a scientific challenging for climatic change studies using MSLP trends, and the split between large‐scale and convective rainfall would also have merits globally to understand if the differences between the two reanalysis data sets are global or if we see convergence on key areas, such as tropices and frontal systems.

Impacts of climate change under CMIP5 RCP scenarios on streamflow in the Huangnizhuang catchment - Fen Ouyang; Yonghua Zhu; Guobin Fu; Haishen Lü; Aijing Zhang; Zhongbo Yu; Xi Chen (Stochastic Environmental Research and Risk Assessment, 2015)

Recent changes in precipitation extremes in the Heihe River basin, Northwest China - Aifang Cheng; Qi Feng; Guobin Fu; Jiankai Zhang; Zongxing Li; Meng Hu; Gang Wang (Advances in Atmospheric Sciences, 2015)

Spatial–temporal variations of spring drought based on spring-composite index values for the Songnen Plain, Northeast China - Xiaoyan Song; Lijuan Li; Guobin Fu; Jiuyi Li; Aijing Zhang; Wenbin Liu; Kai Zhang (Theoretical and Applied Climatology, 2014)

Projection of future rainfall for the North China Plain using two statistical downscaling models and its hydrological implications - Wenbin Liu; Guobin Fu; Changming Liu; Xiaoyan Song; Rulin Ouyang (Stochastic Environmental Research and Risk Assessment, 2013)

A comparison of three multi-site statistical downscaling models for daily rainfall in the North China Plain - Wenbin Liu; Guobin Fu; Changming Liu; Stephen P. Charles (Theoretical and Applied Climatology, 2013)

Partial antiviral activities of the Asn631 chicken Mx against newcastle disease virus and vesicular stomatitis virus - Bichun Li; Dezhi Fu; Yani Zhang; Qi Xu; Ligang Ni; Guobin Chang; Mengmeng Zheng; Bo Gao; Huaichang Sun; Guohong Chen (Molecular Biology Reports, 2012)

Assessments of Impacts of Climate Change and Human Activities on Runoff with SWAT for the Huifa River Basin, Northeast China - Aijing Zhang; Chi Zhang; Guobin Fu; Bende Wang; Zhenxin Bao; Hongxing Zheng (Water Resources Management, 2012)

Evaluation of two statistical downscaling models for daily precipitation over an arid basin in China - Zhaofei Liu; Zongxue Xu; Stephen P. Charles; Guobin Fu; Liu Liu (International Journal of Climatology, 2011)
Two statistical downscaling (SD) models, the nonhomogeneous hidden Markov model (NHMM) and the statistical down‐scaling model (SDSM), which have been widely applied and proved skillful in terms of downscaling precipitation, were evaluated based on observed daily precipitation over the Tarim River basin, an arid basin located in China. The evaluated metrics included residual functions, correlation analyses, probability density functions (PDFs) and distributions. Overall, both models exhibited stability with little model performance difference between the calibration and validation periods. There was little difference for model performance on dry‐spell length (dsl) and wet‐spell length (wsl) between NHMM and SDSM. NHMM showed skill in simulating wet‐day precipitation amount (wpa), whilst SDSM performed relatively poorly on extreme values of wpa, especially for dry stations with annual precipitation lower than 200 mm. Both NHMM and SDSM captured the spatial distribution characteristics of precipitation for most of the stations, as 11 months had an at‐station correlation coefficient being greater than 0.9 and 0.8 for NHMM and SDSM in calibration period. NHMM showed slightly better model performance than SDSM on simulating monthly precipitation, as the former was able to model precipitation well for all months, whereas the later was well only for certain months. SDSM was able to capture the inter‐site correlation characteristics of observed series, whilst the NHMM multi‐site simulation over estimated inter‐site correlation. Both NHMM and SDSM had less skill downscaling annual series because of stochastic components in precipitation amounts modelling. Copyright © 2011 Royal Meteorological Society

Temporal variation of wind speed in China for 1961–2007 - Guobin Fu; Jingjie Yu; Yichi Zhang; Shanshan Hu; Rulin Ouyang; Wenbin Liu (Theoretical and Applied Climatology, 2011)

Evaluation of various root transformations of daily precipitation amounts fitted with a normal distribution for Australia - Guobin Fu; Neil R. Viney; Stephen P. Charles (Theoretical and Applied Climatology, 2010)

A critical overview of pan evaporation trends over the last 50 years - Guobin Fu; Stephen P. Charles; Jingjie Yu (Climatic Change, 2009)

Hydro-Climatic Trends of the Yellow River Basin for the Last 50 Years - Guobin Fu; Shulin Chen; Changming Liu; Dawn Shepard (Climatic Change, 2004)